Tech-Driven Care: Boosting Nurse Home Visit Impact Through Innovation - Rahmat, Rahmat; Afifah, Husna Ainul (GUYUB: Journal of Community Engagement, 2025)
Home visit services at community health centers (Puskesmas) are a key strategy for improving access and the quality of care for chronic patients in the community. However, these services still face administrative challenges, such as manual documentation processes, delays in reporting patient data, and suboptimal team coordination due to limited human resources. This Community Service Program (PKM) was initiated to address these issues by implementing a digital-based Nursing Management System (NMS) to enhance the efficiency and effectiveness of home visit services at Puskesmas Majalaya. The method used was a participatory approach, consisting of four stages: (1) needs analysis through interviews and field observations, (2) development of a web-based application using Laravel tailored to home visit workflows, (3) training and mentoring of nursing staff on system usage, and (4) evaluation using the System Usability Scale (SUS) combined with service performance indicators. The results demonstrated a significant reduction in documentation time (from 40 minutes to 12 minutes per visit), increased completeness of patient family data—including digital genograms, family medical history, and environmental risk factors (from 53% to 95%)—and improved patient adherence to follow-up visit schedules (from 68% to 90%). The utilization of the digital-based NMS has proven to improve administrative efficiency, optimize coordination among home care teams, and enhance service quality. Therefore, it is recommended that this system be adopted more widely across other primary healthcare facilities.